GAMBARAN PASIEN INTUSUSEPSI DI BANGSAL BEDAH ANAK RSUD ARIFIN ACHMAD PEKANBARU PERIODE JANUARI 2009 –DESEMBER 2013 - M. Hadrian Priatna; Huriatul Masdar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Intussusception is the telescoping of one portion of intestine into another. It is one most common cause of intestinal obstruction in children and infants. This retrospective descriptive study was carried out to evaluate the profile of children with intussusception at Pediatric Surgery Unit Arifin Achmad General Hospital Pekanbaru period of January 2009-December 2013 and the data source were medical records. Twenty patients were found reported intussusception, 65% males and 35% females, with 95% found at 3-12 months age range. Sixteen patients (80%) had >24 hours onset with average 63,53+23.912 hours. Four people (20%) patients had a history of coinciding gastroenteritis, and 1 patient (5%) had a history of coinciding respiratory tract infection. The most common symptoms at presentation were currant jelly stool (17 patients), and then 10 patients had abdominal pain and 10 patients presence of abdominal mass. It was reported 2 ileocaecal, 1 colocolical and 17 had no significant data about location of intussusception. All patients had surgical intervention. Eighty per cent patients were recovered, 15% not yet recovered and other had no significant data about output resume.Keywords: intussusception, profile